From Markets to Stakeholders: Toward a Conceptual Model of Political Stakeholder Orientation. Issue 4 (1st October 2020) - Ormrod, Robert P.
Abstract : Since the first publication of the conceptual model of political market orientation model has been used empirically to understand the behavior and attitudes of political party members towards stakeholders in various contexts. The results have provided only limited support for the constructs that represent orientations towards the various stakeholder groups. This has led to an evolution in the conceptualization of the stakeholders that are included in the PMO model across existing literature with the aim of addressing this problem; whilst the inclusion of voters, party members and competing parties have received a degree of support across empirical investigations, it has proved difficult to usefully conceptualize other stakeholder groups. The research aim of this paper is to integrate recent advances in the theoretical foundations of political marketing with conceptual model of PMO in order to propose a revised conceptualization of a political stakeholder orientation. This aim is motivated by a need to further develop the conceptual foundations of the political marketing research field. This paper discusses recent research into the nature of stakeholders in the political marketing context and of the nature of the political exchange of value as a series of three, linked interactions. We subsequently present and critique the stakeholder orientation constructs of the PMO model. Finally, we demonstrate how these recent advances in the political marketing literature necessitate the development of the PMO concept into a broader PSO concept, based on a stakeholder perspective on political marketing.